Os nexos conceituais, a ludicidade e as ações coletivas no processo de aprendizagem de Geometria no Clube de Matemática - Freitas, Jackeline Rossane Garcia de (2022)
This research analyzes the relationship between the way in which mathematics teaching is organized for the early years of elementary school, through Learning Trigger Situations (SDA's) that consist of an organized system. This system allows students to appropriate fundamental knowledge through their actions and operations, as well as the appropriation of conceptual nexus of Geometry from Clube de Matemática (CluMat), an organized and intentionally oriented learning space for students in the 1st phase of Elementary School. Guided by the principles of Historical-Cultural Theory, Activity Theory and Guiding Teaching Activity, this study aims to investigate the evidence of appropriation of conceptual nexus of Geometry by students of the 4th year of Elementary School of a public school municipal, with the development of SDA's in CluMat. A didactic experiment was used as a research methodology, in which the learning of geometry in CluMat through the SDA's will be analyzed and, if they provide the movement, from the collective to the individual, of the construction of geometric theoretical thought and the appropriation of nexuses concepts of geometry by CluMat participants. We seek to understand our research object through the children's oral and written man ifestations in the CluMat Meetings held weekly, totaling 11 meetings. Such manifestations were registered through audiovisual recordings, photographic records, observation, field diary, record sheet and conversation wheel. This data production supported the search for answers to the research question, namely: What are the signs of appropriation of the conceptual nexus of Geometry by stu dents participating in CluMat? To unveil the phenomenon, an analysis was carried out based on the concept of units proposed by Vigotski (2001). Thus, three units were used, namely: 1) collective actions and reflections in the learning space; 2) playfulness as a characteristic in the organization of situations that trigger learning and 3) evidence of appropriation of knowledge about Geometry through SDA's. The movement of analysis allowed us to infer that the children presented a reformu lation of solution strategies, through the sharing of ideas and the re-elaboration of individual actions in favor of the common goal; that there were manifestations of actions with different qualities among the participants, to which part oriented to the search for knowledge, while others were not involved by the playful actions and, revealed indications of appropriation of geometric conceptual nexuses in a development that started from observation to the need to a geometric language. Nevertheless, the final result of this process consists of a teaching organization that, in a way, valued observation and geometric abstraction based on empiricism.